The role of low level laser therapy on the expression of IL_1 beta in wound healing - Warkaa M Al-Wattar; Bashar H Abdulluh; Ali S Mahmmod (College of Dentistry/ University of Baghdad, 2014)
Background: Low-level laser therapy (LLLT) has been extensively applied to improve wound healing due to some biostimulatory properties presented by laser arrays apparently able to accelerate the repair of soft tissue injuries. However, the role of proinflammatory interlukines not been studied yet. IL_1 ? represent one of the most important poroinflammatory interlukines that involved in wound healing. The goal of this study was to investigate the effect of 790-805nm diode laser on the expression of IL_1 ? during wound healing in mice. Materials and Methods: Standard-sized wounds (1.5cm) were carried out in the face of 96 white albino mice. Half of them underwent LLLT treatment (360 J/cm 2) at 790-805 nm delivered immediately after wound procedure. The repairing area was removed and stained with immunohistochemistry technique to detect the expression of IL_1 ?. Results it had been found that LLLT was able to increase the expression of the IL_1 ? in early phases of healing as well as to enhance epithelization remodeling process at both 7 th and 14 th days of wound healing. Conclusions : The LLLT protocol tested in this study resulted in increased the expression of IL_1 ? in the lased group significantly at day 7 of healing period which affect wound healing.